Gellan Gum Based Sol-to-Gel Transforming System of Natamycin Transfersomes Improves Topical Ocular Delivery - Janga, Karthik Yadav; Tatke, Akshaya; Dudhipala, Narendar; Balguri, Sai Prachetan; Ibrahim, Mohamed Moustafa; Maria, Doaa Nabih; Jablonski, Monica M.; Majumdar, Soumyajit (The Journal of pharmacology and experimental therapeutics, 2019)
Short precorneal residence time and poor transocular membrane permeability are the major challenges associated with topical ocular drug delivery. In the present research, the efficiency of the electrolyte-triggered sol-to-gel–forming system of natamycin (NT) transfersomes was investigated for enhanced and prolonged ophthalmic delivery. Transfersomes were optimized by varying the molar ratios of phospholipid, sorbitan monostearate (Span) and tocopheryl polyethylene glycol succinate (TPGS). NT transfersome formulations (FNs) prepared with a 1:1 molar ratio of phospholipid-to-Span and low levels of TPGS showed optimal morphometric properties, and were thus selected to fabricate the in situ gelling system. Gellan gum–based (0.3% w/v) FN-loaded formulations (FNGs) immediately formed an in situ gel in the simulated tear fluid, with considerable viscoelastic characteristics. In vitro cytotoxicity in corneal epithelial cells and corneal histology studies demonstrated the ocular safety and cytocompatibility of these optimized formulations. Transcorneal permeability of NT from these formulations was significantly higher than in the control suspension. Moreover, the ocular disposition studies of NT, from the FNs and FNGs, in New Zealand male albino rabbits demonstrated the superiority of the electrolyte-sensitive FNGs in terms of NT delivery to the ocular tissues.